HYPONATREMIA IN A GROUP OF IRAQI PATIENTS WITH STROKE (Iraqi Journal of Medical Sciences, 2016)
Background: Hyponatremia is a common electrolyte disorder encountered in patients of stroke, which is usually either due to inappropriate secretion of antidiuretic hormone (SIADH) or cerebral salt wasting syndrome (CSWS). Making an accurate diagnosis is important because the treatment of each condition is quite different. Objectives:We conducted this study to determine the incidence and etiology of hyponatremia in patients of stroke.Methods:A cross sectional study of 100 patients diagnosed to have stroke (50 ischemic, 50 hemorrhagic) based on clinical history, examination and brain images. Patients were evaluated for hyponatremia (serum sodium < 135 mmol/L) during the second week of their admission. Results:Out of 100 patients, 17 patients had hyponatremia, all Patients with serum sodium level in hyponatremic range were limited to patients with hemorrhagic stroke, while no patients with ischemic stroke had a low serum sodium level, this difference was significantly different, P-value was < 0.001.Conclusion:Incidence of hyponatremia in our study population was 17%, all Patients with hyponatremia were limited to patients with hemorrhagic stroke, in patients of hyponatremia; 82% were having SIADH and 18% were having CSWS.Keywords: Hyponatremia, ischemic stroke, hemorrhagic stroke, syndrome of inappropriate antidiuretic hormone, cerebral salt wasting syndrome.
Keywords: Hyponatremia; ischemic stroke; hemorrhagic stroke; syndrome of inappropriate antidiuretic hormone; cerebral salt wasting syndrome